The Reve’s Puzzle Revisited: Reve’s Puzzle Revisited - Majumdar, Abdullah-Al-Kafi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The Reve’s puzzle, introduced by the English puzzlist, H.E. Dudeney, is a mathematical puzzle with 10 discs of different sizes and four pegs, designated as S, P1, P2 and D. Initially, the n (  1) discs rest on the source peg, S, in a tower (with the largest disc at the bottom and the smallest disc at the top). The objective is to move the tower from the peg S to the destination peg D, in a minimum number of moves, under the condition that each move can transfer only one disc from one peg to another such that no disc can ever be placed on top of a smaller one. This paper considers the solution of the dynamic programming equation corresponding to the Reve’s puzzle.